Justice through polycentricity? a critical examination of climate justice framings in Pakistani climate policymaking - Shawoo, Z; McDermott, C (Taylor and Francis, 2020)
The purpose of this study is to investigate the extent to which the existence of a polycentric climate governance regime in Pakistan has enabled diverse framings of climate justice to emerge and be operationalized within policymaking. A two-part analysis is conducted through systematic coding and textual analysis of interview transcripts and policy documents. Firstly, an analysis based on climate justice framings reveals that, whilst national governmental actors predominantly adopt an international framing of climate justice, non-state actors have increasingly adopted vulnerability, human rights and transformational framings of justice, thereby supporting the theory that polycentricity is widening the space for voicing diverse framings. Secondly, a polycentric governance-based analysis reveals that several institutional barriers limit the ability of non-state actors to operationalize these framings, particularly capacity and resource constraints, limits of scale and scope, changing legislation and the unequivocal power held by the state. Hence, Pakistan’s overarching climate change strategy prioritizes justice between countries, while obscuring domestic inequalities, poverty and vulnerability, which are only addressed by non-state actors through isolated activities rather than in a coordinated manner within national policy. This finding suggests that polycentric governance can diversify climate discourse, but also that the intergovernmental climate regime may reinforce the nation state’s international framings of justice at the expense of domestic justice concerns.